CONSTRUCTING CHARTS QUALITY OF DIGITAL DEVICES WITH THE PHASE CONTROL - D. P. Kukin; V. N. Prigara (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Principles of operation of digital devices with a phase control are considered. The method of arguments select of system ground the exactitude requests, switching on constructing of charts of quality and allowing for diverse kinds of nonlinearity of characteristics of constituent units is tendered. The tendered method is illustrated on an instance of a select of sampling rate of the digital device.